A Preliminary Study on the Pattern, the Physiological Bases and the Molecular Mechanism of the Adductor Muscle Scar Pigmentation in Pacific Oyster Crassostrea gigas - Yu, Wenchao; He, Cheng; Cai, Zhongqiang; Xu, Fei; Wei, Lei; Chen, Jun; Jiang, Qiuyun; Wei, Na; Li, Zhuang; Guo, Wen; Wang, Xiaotong (Frontiers in Physiology, 2017)
The melanin pigmentation of the adductor muscle scar and the outer surface of the shell are among attractive features and their pigmentation patterns and mechanism still remains unknown in the Pacific oyster Crassostrea gigas. To study these pigmentation patterns, the colors of the adductor muscle scar versus the outer surface of the shell on the same side were compared. No relevance was found between the colors of the adductor muscle scars and the corresponding outer surface of the shells, suggesting that their pigmentation processes were independent. Interestingly, a relationship between the color of the adductor muscle scars and the dried soft-body weight of Pacific oysters was found, which could be explained by the high hydroxyl free radical scavenging capacity of the muscle attached to the black adductor muscle scar. After the transcriptomes of pigmented and unpigmented adductor muscles and mantles were measured with RNAseq and compared, it was found that the retinol metabolism pathway were likely to be involved in melanin deposition on the adductor muscle scar and the outer surface of the shell, and that the different members of the tyrosinase or Cytochrome P450 gene families could play a role in the independent pigmentation of different organs.